8-Hydroxyquinolines: a review of their metal chelating properties and medicinal applications - Prachayasittikul V; Prachayasittikul S; Ruchirawat S; Prachayasittikul V (Dove Medical Press, 2013)
Veda Prachayasittikul,1 Supaluk Prachayasittikul,2 Somsak Ruchirawat,3 Virapong Prachayasittikul11Department of Clinical Microbiology and Applied Technology, Faculty of Medical Technology, 2Center of Data Mining and Biomedical Informatics, Faculty of Medical Technology, Mahidol University, Bangkok, Thailand; 3Laboratory of Medicinal Chemistry, Chulabhorn Research Institute and Chulabhorn Graduate Institute, Bangkok, ThailandAbstract: Metal ions play an important role in biological processes and in metal homeostasis. Metal imbalance is the leading cause for many neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, and multiple sclerosis. 8-Hydroxyquinoline (8HQ) is a small planar molecule with a lipophilic effect and a metal chelating ability. As a result, 8HQ and its derivatives hold medicinal properties such as antineurodegenerative, anticancer, antioxidant, antimicrobial, anti-inflammatory, and antidiabetic activities. Herein, diverse bioactivities of 8HQ and newly synthesized 8HQ-based compounds are discussed together with their mechanisms of actions and structure–activity relationships.Keywords: metal binding compound, antineurodegenerative, anticancer, antidiabetic, multifunctional actions, structure–activity relationships